Adenovirus 21 Infection in an Isolated Antarctic Station: Transmission of the Virus and Susceptibility of the Population - Shult, Peter A.; Polyak, Frank; Dick, Elliot C.; Warshauer, David M.; King, Lenard A.; Mandel, Adrian D. (Oxford University Press, 1991)
Natural dissemination of viral respiratory illness to susceptible men may occur with surprising difficulty. This was especially evident during a 1977 outbreak of adenovirus type 21 (Ad-21) at McMurdo Station, a US research base in Antarctica. The unique circumstances at McMurdo allowed 125 men from the US to join and intermingle with 75 men who had wintered for 6 months in complete isolation. For an additional 5-week (September 2 to October 4, 1977) isolation penod, respiratory illness etiology and transmission were monitored in the combined population. A total of 89% of the population was susceptible (neutralizing antibody titer, <1:3) to Ad-21 but only 15.0% were infected. Illness spread very slowly (1.5 cases/100 persons/week) with no epidemic peak and was much less severe than Ad-21 outbreaks in other settings. The incidence of infection (17.3%) and illness (9.6%) was low even in men who had wintered over, with values very similar to those of the newcomers (13.9% and 8.9%, respectively). Thus, despite a harsh environment and frequent prolonged gatherings of susceptible personnel, even a respiratory virus type with known epidemic potential was surprisingly difficult to transmit.